Achieving dynamic behaviour and thermal expansion in the organic solid state via co-crystallization1. Issue 8 (14th August 2015) - Hutchins, Kristin M.; Groeneman, Ryan H.; Reinheimer, Eric W.; Swenson, Dale C.; MacGillivray, Leonard R.
<x xml:space="preserve">Abstract</x> Molecular motion of an azo functional group is 'unlocked' via co-crystallizations.